Implementing New Marketing Strategies in the Context of the Online Environment – Advantages, Disadvantages, Statistics and Trends - Dumitrescu, L.; Fuciu, M.; Gorski, H. (Київський національний університет імені Тараса Шевченка, 2018)
In the context of the online environment and the pressure created by the new information and communication technologies, when the Internet is used by more than 40% of the world population, when the penetration rate of the online has reached more than 75% in Europe (52% in Romania) and almost 90% in North America and when the smartphone has become a constant companion of the individuals, today's companies must adapt or develop new marketing strategies that will help them win and retain the consumers, otherwise they will slowly perish. This paper aims to present several important marketing strategies based on the usage of the Internet tools like: search engine optimisation (SEO), content marketing, social media/online social networks, email marketing, lead generation, sales etc., that can be implemented by the Romanian companies. We are presenting several important advantages and disadvantages of these marketing strategies. We will also bring forth several important statistics regarding the Internet usage and of the online marketing tools and we shall underline future trends related to these aspects, all this being designed to support future managerial decisions and to better understand the need for the companies to implement and use them successfully.

У контексті онлайн-середовища й тиску, створеного новими інформаційними та комунікаційними технологіями, коли Інтернетом користується понад 40% населення світу, коли рівень проникнення в Інтернет у Європі досяг більш ніж 75% (52% у Румунії) і майже 90% у Північній Америці, і коли смартфон став постійним супутником окремих осіб, сьогоднішні компанії повинні адаптувати або розробляти нові маркетингові стратегії, які допоможуть їм вигравати і зберегти споживачів, інакше ці компанії поволі щезнуть. Тому метою є представлення кількох важливих маркетингових стратегій, що базуються на використанні румунськими компаніями таких інструментів Інтернету, як оптимізація пошукової системи (SEO), контент-маркетинг, соціальні мережі / соціальні мережі в Інтернеті, маркетинг електронної пошти, продажі тощо. Показано кілька важливих переваг та недоліків цих маркетингових стратегій. Також наведено кілька важливих статистичних даних стосовно використання Інтернету та інструментів онлайнового маркетингу й підкреслено майбутні тенденції, пов'язані з цими аспектами. Усе це призначено для підтримки майбутніх управлінських рішень і кращого розуміння необхідності їх упровадження та успішного використання компаніями.
Упровадження нових маркетингових стратегій у контексті Інтернет-середовища: переваги, недоліки, статистика та тенденції
Keywords: online marketing; marketing strategies; internet; social media; інтернет-маркетинг; маркетингові стратегії; інтернет; соціальні мережі